Comparison of maternal and fetal outcomes in gestational diabetes mellitus diagnosed either by oral glucose tolerance test or diabetes in pregnancy study group India - Sinha, Somya; Mayadeo, Niranjan M. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Background: The optimal strategy for screening and diagnosis of Gestational Diabetes Mellitus (GDM) is still controversial and elusive. There is possibility of difference in maternal and fetal outcome depending on the diagnostic method used. This study throws light on the efficacy of two screening tests “Oral Glucose Tolerance Test’’ and “Diabetes in Pregnancy Study Group India” and to know maternal and fetal outcome in pregnancy complicated by GDM in Indian setting. Methods: Depending on the diagnostic method used 100 GDM patients were divided in 2 groups: 1. OGTT, 2. DIPSI. Maternal outcomes were measured in terms of pregnancy induced hypertension, polyhydramnios, preterm labour, genital tract injury and methods of termination of pregnancy, gestational age at delivery. Congenital malformation, macrosomia, hypoglycemia, hyperbilirubinimia, respiratory distress, duration of NICU stay was studied in newborns. Results: 22% of DIPSI group and 26% of OGTT group had PIH as comorbidity. Preterm delivery was noted in 22% of DIPSI group and 30% of OGTT group. 50% patients of both the groups underwent LSCS. No intrapartum complications were seen in 82% of patients. Malformations were noted in 18% of DIPSI group and 14% of OGTT group. In DIPSI group 14% of baby had macrosomia compared to 10% and in that of OGTT group. In neonates, hypoglycaemia, respiratory distress syndrome and hyperbilirubinemia seen in 46.8%, 31% and 42.6% respectively in DIPSI group compared to 50%, 45.5% and 47.7% respectively in OGTT group. Conclusions: No statistically significant difference was noted with respect to maternal and fetal outcomes between the two groups.